Use and awareness of emergency hormonal contraception in university students (2022)
To understand the use and awareness of EHC among university students. This cross-sectional descriptive observational study with a quantitative approach was conducted with a random sample of university students from Villavicencio using a self administered survey. A description of the variables was performed, followed by a multinomial regression to evaluate possible associations with the non-use of HEC, obtaining OR. A total of 273 students were surveyed, out of whom 95.97% stated that they were aware of emergency hormonal contraception (EHC) and 4.03% were unaware. 59.34% students had previously used EHC, whereas 40.66% had not. On evaluation of the respondents’ knowledge regarding EHC, it was found that 135 students (49.45%) possessed an acceptable level of knowledge of EHC, whereas 138 students (50.55%) did not pass the evaluation and possessed a very low level of knowledge regarding EHC. It is suggested in the results that there is more predisposition to the use of the EHC method in women (OR 1.89 CI 1.15-3.09, p=0.00009), and in those who have received counseling on contraception (OR 3.09 CI 1.88-5.07, p= 0.0000016. The results of the survey suggest that the existing education and communication strategies regarding sexuality and contraceptive use for adolescents and young adults should be rethought.